Effectiveness of Peppermint (Menta piperita) and Nutmeg (Myristica fragrans) Essential Oil on Mortality of Storage Pest Tribolium castaneum - Barna Deta Cristin Naftaly; Wiwin Windriyanti; Trijanti A. Widinni Asnan; Ramadhani Mahendra Kusuma (Nusantara Science and Technology Proceedings, 2023)
Tribolium castaneum commonly known as the red flour beetle, stands as a significant stored insect pest, inflicting crucial damage upon stored commodities. The infestations by T. castaneum result in substantial losses both in terms of quality and quantity of the stored products. The use of essential oils presents itself as an alternative pest control strategy, functioning as fumigants that can effectively thwart reinfestations of these pests during storage periods. This research was conducted to ascertain the efficacy of peppermint (Mentha piperita) and nutmeg (Myristica fragrans) essential oils in the management of the stored insect pest T. castaneum. The essential oil assessment was carried out utilizing the fumigation technique within Petri dishes, employing various concentrations of 1%, 2%, 2%, 4%, and 5%. Observations on T. castaneum mortality were conducted after 72 hours post-treatment (HAT). The results obtained at the 72 HAT juncture exhibited the highest mortality rate of T. castaneum within the treatment using a 5% concentration of peppermint essential oil, yielding a mortality rate of 90%. In contrast, the highest mortality rate for the nutmeg essential oil treatment was recorded at 48% within the 5% concentration. Thus, it can be concluded that the application of a 5% concentration of peppermint essential oils proves to be effective in controlling the T. castaneum infestation